Characteristics and patterns of pediatric chemotherapy-induced peripheral neuropathy: A systematic review. (2021) - Smith, Ellen M. Lavoie; Kuisell, Clare; Cho, Youmin; Kanzawa-Lee, Grace A.; Gilchrist, Laura S.; Park, Susanna B.; Scott, Mary R; Alberti, Paola; ,
Abstract/Summary: This systematic review provides a high-quality synthesis of the empirical evidence regarding chemotherapy-induced peripheral neuropathy (CIPN) characteristics and patterns described in studies of children who received neurotoxic chemotherapy to treat cancer. PubMed, CINAHL, PsycINFO, and Embase were searched for articles published 2009 - 2019, yielding 861. Forty-two papers met the eligibility criteria, including 31 that described characteristics and patterns of vincristine-induced CIPN. Fifty-seven percent of articles were of low to moderate quality; measurement flaws were the most common limitations. The reported CIPN incidence varies widely (2.8%–100%) depending on risk factors (e.g., race) and the measurement approach. Incidence rates of sensory, motor, autonomic CIPN, and pain were 12–28%, 50–72%, 0.8–83% and 5.7–44%, respectively. The evidence suggests that sensory and motor neuropathy, pain, and functional deficits are common and can persist into adulthood. Caucasian race is a risk factor and, contrary to prior thinking, cumulative chemotherapy dosage alone does not predict CIPN severity. The influence of other risk factors is less clear, and studies to date have not explored potential interactions among race, genetics, age, sex, drug metabolism, and nutritional status, among other factors.